Effect of Cu on corrosion behavior of low alloy steel under the simulated bottom plate environment of cargo oil tank. (June 2017) - Hao, Xuehui; Dong, Junhua; Wei, Jie; Etim, Ini-Ibehe Nabuk; Ke, Wei
Highlights: Residual cementite enhances micro-galvanic corrosion for 16Mn and 16MnCu steels. Nano-sized Cu particle is deposited on the steel surface during corrosion process. Galvanic corrosion is restrained by the deposited Cu. Abstract: The effect of Cu on the corrosion behavior of low alloy steel under the simulated bottom plate environment of cargo oil tank was investigated by using gravimetric test, SEM, EDS, XPS, XRD and electrochemical measurements. The results indicate that the corrosion resistance of 16MnCu steel was higher than that of 16Mn steel, which was related to the deposition of nano-sized Cu particles on the surface. The deposited Cu might suppress both the anodic dissolution of the ferrite and hydrogen evolution reaction on the cementite, leading to the reduction of the galvanic effect caused by the residual cementite.